In situ bioreclamation : applications and investigations for hydrocarbon and contaminated site remediation - Hinchee, Robert E.; Olfenbuttel, Robert F. (Butterworth-Heinemann, 1991)
In Situ Bioreclamation: Applications and Investigations for Hydrocarbon and Contaminated Site Remediation is a collection of selected papers submitted by participants to the international symposium """"In Situ and On-Site Bioreclamation"""", held in San Diego, California in March 1991. The book consists of articles, which represent a substantial technical contribution, and technical notes, and brief technology descriptions or reports of preliminary or less substantial studies that proposes and exposes various solutions for the biological treatment of contaminated soil, water, and gas. This vol